The Inspiration of “Hot and Cold Media” Theory to Flat Style Design - Liao, Xiaofeng (Art & Design Research, 2021)
With the rapid development of the Internet, simple flat style arises at the right moment and is widely used. However, flat style is criticized for its homogeneity and difficulty in understanding. Flat design, as one of the design methods, is a communication medium to improve the efficiency of communication. Based on McLuhan’s “hot and cold medium” theory, this paper analyzes the characteristics of flat design style. Flat design should properly combine the characteristics of skeuomorphic style; Enhance flattening participation; To improve the efficiency of understanding and promote the scientific development of flat design.